Penerapan Media Gambar Berseri untuk Meningkatkan Karangan Narasi Pada Siswa Sekolah Dasar - Muti Umanahu; Nurbaya Taufik; Pipit A. Susanti (Peneliti.net, 2021)
This study aims to reveal the ability to write narrative essays through picture series media. This research was conducted using classroom action research with two cycles. The data analysis technique is a qualitative descriptive technique. The research subject is class IV SDN 1 Patani, 2018/2019 academic year with 18 students as subjects. The results of the research cycle 1, student learning completeness is 52.94%. Cycle II to 87.25%, an increase of 35.30%. It was concluded that the application of serial image media in writing narrative essays made it easier for students, both in pre-writing, writing, and revising. In addition, improving students' critical, systematic, and reflective thinking skills.